"Green" environmental crazing of polymers in oil-in-water emulsions with high water content. (9th January 2020) - Arzhakova, O.V.; Kopnov, A. Yu; Nazarov, A.I.; Dolgova, A.A.; Volynskii, A.L.
Abstract: This work addresses "green" environmental crazing of polymers in biphase oil-in-water (O/W) emulsions with high water content (above 95 vol %), which can serve as an ecologically safe alternative to pure organic solvents (hydrocarbons and aliphatic alcohols as oils) with respect to their effect on the mechanical behavior of polymers and stress-induced development of porosity via environmental crazing. This approach is shown to be universal for both modes of environmental crazing as intercrystallite crazing for semicrystalline (high-density polyethylene, polytetrafluoroethylene) and classical crazing for amorphous glassy polymers (PET). The mechanism behind the action of the O/W emulsions on polymers is discussed. The applied advantages of the use of the O/W emulsions with high water content for the preparation of mesoporous and nanocomposite polymer materials are highlighted. Graphical abstract: Image 10683890 Highlights: "Green" crazing of polymers in the O/W emulsions with high water content is studied. With respect to polymers, the O/W emulsions are shown to behave as pure solvents. The mechanism behind the action of the O/W emulsions on polymers is proposed. Applied aspects of the use of the O/W emulsions are discussed.